10 Book Notices - Dharma, Journal of (Journal of Dharma, 1999)
1. Dr.PasangYontenAryaDictionaryofTibetanMateriaMedica. translatedfromTibetanandeditedbyDr.YontenGyastso,Delhi: MotilaiBanarsidass,1998,pp.xv+SlO,Rs.395.ISBN:81-208-1567-x. 2. CharlesBreaux,JourneyintoConsciousness. andJungianPsychology,Delhi:Motilal pp.xviii+254,Rs.175.00.ISBN:81-208-1454-1. TheChakras,Tantra Banarsidass. 3. RobertSvobodaandArnieLade,ChineseMedicineandAyurveda, ForewordbyMichaelTierra,O.M.D.,Delhi:MotilalBanarsidass,1998, pp.155,Rs.150.00.ISBN:81-208-1472-x. 4. RaimonPanikkar,TheCosmotheandricExperience.Emerging ReligiousConsciousness,editedwithintroductionbyScottEastham, Delhi:MotilalBanarsidass,FirstIndianEdition1998,pp.xv+160, Rs.250.00.ISBN:81-208-1340-5. 5. Roy Eugene Davis, Living in God. 366 Themes for Daily Meditative Contemplation and Spiritual Enrichment Through the Year with Lifeenhancing Affirmations and Inspirational Quotations, Delhi: Motilal Banarsidass, 1998, pp.159, Rs.95.00 (paper). ISBN: 81-208-1544-0. 6. Hedwig Lewis, S.J., Mirrors of Life, Anand: Gujarat Sahitya Prakash, 1998, pp.viii+lvo, Rs.70.00; 10.00 7. Hedwig Lewis, S.J., Mirrors for the Heart, Anand: Gujarat Sahitya Prakash, 1998, pp.xvi+182, Rs.70.00; 10.00. 8. Hedwig Lewis, S.J., Images of Mirrors, Anand: Gujarat Sahitya Prakash, 1998, pp.xii+ 178, Rs.67.00; 10.00. 9. Dr. George Bishop, In Search of Cathay. The Travels of Bento de Goes, S.J., Anand: Gujarat Sahitya Prakash, pp.xiii+306. 10. Howling Wolf, Kafka in Samadhi, New York: Black Sun Press, 1998, pp.149. ISBN: 0-553-21193-7.